THE INFLUENCE OF CIVIC EDUCATION SUBJECTS IN PREVENTING BULLYING BEHAVIOR IN CLASS X STUDENTA AT SMA NEGERI 3 BOJONEGORO: Pengaruh Mata Pelajaran Pendidikan Kewarganegaraan Dalam Mencegah Perilaku Bullying Pada Siswa Kelas X Di Sma Negeri 3 Bojonegoro - Putri Fitria Silaturrokhimi; Neneng Rika Jazilatul Kholidah; Fifi Zuhriah (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines the influence of Civic Education in preventing bullying behavior among 10th-grade students at SMA Negeri 3 Bojonegoro. The background highlightsthe increasing cases of bullying in edecational environments and the strategic role of Civic Education in shaping students’ character through values like tolerance, empathy, and social responsibility. The research aims to determine the extent to which Civic Education impacts bullying prevention. Using a quantitative approach, data were collected through questionnaires from 36 students and analyzed using simple linear regression. Results indicate a singnificant negative correlation (t = -9.630, p = 0.000), showing that higher understanding of Civic Education reduces bullying tendencies. The study concludes that Civic Education effectively fosters anti-bullying attitudes among students.